Effect of incorporation of 2-tert-butylaminoethyl methacrylate on flexural strength of a denture base acrylic resin - Paleari, André Gustavo [UNESP]; Marra, Juliê [UNESP]; Pero, Ana Carolina [UNESP]; Rodriguez, Larissa Santana [UNESP]; Ruvolo-Filho, Adhemar; Compagnoni, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2011)
Polymethyl methacrylate (PMMA) resins have commonly been used as a denture base material. However, denture bases may act as a reservoir for microorganisms and contribute to oral diseases in denture wearers. It is hypothesized that the 2-tertbutylaminoethyl methacrylate (TBAEMA) incorporated to acrylic resins should have antimicrobial activity related to the presence of amino groups on acrylic resin surface. Objectives: The objectives of this study were to evaluate the presence of amino groups on acrylic resin surface and the influence on flexural strength after incorporation of TBAEMA. Material and Methods: Six groups were divided according to the concentration of TBAEMA incorporated to acrylic resin (Lucitone 550): 0, 0.5, 1.0, 1.5, 1.75 and 2%. Specimens surface were evaluated by Electron Spectroscopy for Chemical Analysis (ESCA) to detect the presence of amino groups, represented by nitrogen ratios. Flexural strength of the specimens was tested and results were analyzed by ANOVA and Tukey's test (α=0.05). Results: Different nitrogen ratios were observed on specimen surfaces: 0, 0.13, 0.74, 0.66, 0.92 and 0.33% for groups 0, 0.5, 1.0, 1.5, 1.75, and 2%, respectively. Significant differences were found for flexural strength (p<0.001). The mean flexural strength values were 98.3±3.9, 93.3±3.2, 83.9±2.1, 82.8±5.2, 71.2±5.1 and 17.3±3.2 MPa for groups 0, 0.5, 1.0, 1.5, 1.75, and 2%, respectively. Conclusion: Within the limitations of this study, the incorporation of TBAEMA results in the presence of the potentially antimicrobial amino groups on specimen surfaces, but affect the flexural strength, depending on the concentration of TBAEMA.
Keywords: Acrylic resins; Local anti-infective agents; Mechanical stress; Surface properties